Analysis of a nurse-provided on-call peritoneal dialysis support in an outpatient reference care centre - Annemarie Albert; Stefan Richter; Philipp Kalk; Philipp Stieger; Rainer Peter Woitas; Rüdiger C. Braun-Dullaeus; Christian Albert (BMC, 2024)
Abstract Background To analyse the nature of medical or technical emergency issues of ambulatory peritoneal dialysis (PD) patients calling a nurse-provided emergency PD support service of a reference centre that is provided all year in the after-hours. Methods We retrospectively analysed patients' chief complaint, urgency, resolution of and association to current PD treatment and modality directed to an on-call nurse-provided PD support service from 2015-2021 based on routinely collected health data. Calls were systematically categorized being technical/procedural-, medical-, material-related or type of correspondence. Call urgency was categorized to have "immediate consequence", inquiry was eligible for "processing next working day" or whether there was "no need for further action". Call outcomes were classified according to whether patients were able to initiate, resume or finalize their treatments or whether additional interventions were required. Unexpected adverse events such as patients' acute hospitalization or need for nurses' home visits were evaluated and quantified. Results In total 753 calls were documented. Most calls were made around 7:30 a.m. (5:00-9:00; median, 25-75th CI) and 6:30 p.m. (5:00-8:15). 645 calls were assigned to continuous ambulatory- (CAPD) or automated PD (APD). Of those, 430 calls (66.7%) had an "immediate consequence". Of those 77% (N = 331) were technical/procedural-, 12.8% (N = 55) medical- and 6.3% (N = 27) material related issues. 4% (N = 17) were categorized as other correspondence. Issues disrupting the course of PD were identified in 413 cases. In 77.5% (N = 320) patients were able to initiate, resume or finalize their treatment after phone consultation. Last-bag exchange was used in 6.1% enabling continued therapy in 83.6%. In 35 cases a nurse visit at patients' home or patients' visit to the practice at the earliest possible date were required, while hospitalization was required in seven medical category cases (5.4% and 1.09% of total assessed calls, respectively). Conclusion The on-call PD-nurse provides patient support for acute and imminent issues enabling them to successfully initiate, resume or finalize their prescribed treatment. Nurses triage of acute conditions facilitated rapid diagnostics and therapy. Maintaining quality PD homecare, the provision of trained personnel is indispensable. The information gathered in this study may therefore be used as a foundation to tailor educational programs for nephrology nurses and doctors to further develop their competencies in PD.